ACCA Paper P2: Corporate Reporting (International and UK Stream) Practice and Revision Kit - BPP Learning Media Ltd (BPP Learning Media Ltd, 2007)
This Kit provides provides the only study material for Paper 2 Corporate Reporting (International and UK Stream) which has been comprehensively reviewed by the This unique review ensures that the questions, solutions and guidance provide the best and most effective resource for practicing and revising for the exam.
Keywords: Accounting; Corporate Reporting; Non-Fiction; Practice and Revision Kit